211k views
5 votes
Solve for inequality’s. Show your work.


(3х – 2y = 14
( 2x + 2y = 6

Solve for inequality’s. Show your work. (3х – 2y = 14 ( 2x + 2y = 6-example-1
User Atomsfat
by
4.9k points

1 Answer

2 votes
2y = 3x - 14

So 2x + 3x - 14 = 6
5x = 20
x = 4

So now that we know x=4, we plug it into the first equation to solve for Y:

3(4) - 2y = 14
12 - 2y = 14
-2y = 2
y = -1

x = 4
y = -1
User Ryuusenshi
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.